2021
DOI: 10.3390/diagnostics11112153
|View full text |Cite
|
Sign up to set email alerts
|

Multimer Analysis of Von Willebrand Factor in Von Willebrand Disease with a Hydrasys Semi-Automatic Analyzer—Single-Center Experience

Abstract: von Willebrand disease (VWD) is reportedly the most common inherited bleeding disorder. This disorder develops as a result of defects and/or deficiency of the plasma protein von Willebrand factor (VWF). Laboratory testing for VWF-related disorders requires the assessment of both VWF level and VWF activity, the latter requiring multiple assays. As an additional step, an evaluation of VWF structural features by multimer analysis is useful in selective investigations. Multimer analysis is also important for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Astonishingly, vWF antigen and activity were within normal ranges, but the FVIII level was repeatedly between 4 and 5.5%. Extended quantitative and qualitative evaluations of vWF multimers were not performed; they could have given helpful information for the exclusion of vWD type 2 [ 17 ]. The genetic testing revealed a pathogenic hemizygous F8: c.6977 G>A variant, identified in exon 26 of the F8 gene (ref seq NM_000132.3).…”
Section: Resultsmentioning
confidence: 99%
“…Astonishingly, vWF antigen and activity were within normal ranges, but the FVIII level was repeatedly between 4 and 5.5%. Extended quantitative and qualitative evaluations of vWF multimers were not performed; they could have given helpful information for the exclusion of vWD type 2 [ 17 ]. The genetic testing revealed a pathogenic hemizygous F8: c.6977 G>A variant, identified in exon 26 of the F8 gene (ref seq NM_000132.3).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that non-O blood type individuals have higher (approximately 25%) FVIII:C and VWF:Ag than O blood type individuals [ 23 , 24 ]. A recently published single-centre study found that individuals with blood group O had approximately 10–20% lower plasma VWF levels compared to individuals without blood group O [ 25 ]. It has been suggested that the lower VWF:Ag in O blood type individuals is attributable to the susceptibility of VWF to ADAMTS13 proteolysis and the significantly increased hepatic clearance of VWF, which is mediated via the asialoglycoprotein receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Other activities of VWF, such as its binding to collagen, were unaffected by polyP [13]. The multimerization state of VWF, which is decisive for some of its adhesion activities [16,17], also did not change in VWF incubated with polyP or polyP-degrading enzymes [13].…”
Section: Introductionmentioning
confidence: 91%